Posted by **Anonymous** on Tuesday, May 13, 2014 at 12:03pm.

Find the product (1 - 3x) (x^2 - 6x - 4)x^2

A. -3x^5 + 19x^4 + 6x^3 - 4x^2

B. -3x^5 - 19x^4 + 6x^3 - 4x^2

C. -3x^5 + 19x^4 - 6x^3 - 4x^2

D.-3x^5 - 19x^4 - 6x^3 - 4x^2

## Answer This Question

## Related Questions

- Math - Solve the polynomial equation, to obtain the first root. x^3+7x^2+19x+13 ...
- Math - Simplify 1) -6-7(C+10) 64-7C -76-7C** 4-13C -16-13C 2) 5x+6(x-2) -8(x-3) ...
- Pre-Calculus - Rewrite each quadratic equation in the form ax^2+bx+c=0. Then,use...
- Geometry - There showing a diagram and asking for the value of x and y. There is...
- math word problems - (24 cents) per mile. Toyotas rent for $31 per day and $.19...
- algebra - 1)Solve by factoring:5x^2=4-19x answer=-4,1/5 2)Which quadratic ...
- MATH ALGEBRA - f(x)=6x^3+19x^2+8x-5 find all the zeros of the given function
- algebra - solve the equation 5x^2=19x+4 X=
- algebra - How do you work these problems? 8x-7=15+19x 7.6x-3.5x=-65.6 -7x-23=-25...
- Algebra - Factoring with a leading coefficient 3x^2+19x-72

More Related Questions